Systemic Cellular Activation Mapping of an Extinction-Impaired Animal Model - Park, Kwanghoon; Chung, ChiHye (Frontiers in Cellular Neuroscience, 2019)
Fear extinction diminishes conditioned fear responses and impaired fear extinction has been reported to be related to anxiety disorders such as post-traumatic stress disorder (PTSD). We and others have reported that 129S1/SvImJ (129S1) strain of mice showed selective impairments in fear extinction following successful auditory or contextual fear conditioning. To investigate brain regions involved in the impaired fear extinction of 129S1 mice, we systemically analyzed c-Fos expression patterns before and after contextual fear conditioning and extinction. After fear conditioning, 129S1 mice showed significantly increased c-Fos expression in the medial division of the central amygdala (CEm), prelimbic cortex (PL) of the medial prefrontal cortex (mPFC), and dorsal CA3 of the hippocampus, compared to that of control C57BL/6 mice. Following fear extinction, 129S1 mice exhibited significantly more c-Fos-positive cells in the CEm, PL, and paraventricular nucleus of the thalamus (PVT) than did C57BL/6 mice. These results reveal the dynamic circuitry involved in different steps of fear memory formation and extinction, thus providing candidate brain regions to study the etiology and pathophysiology underlying impaired fear extinction.